Framing science in the time of Covid-19 pandemic: Lessons from CNN Philippines’ reportage - Ernesto Cordero Collo, Jr. (Informasi, 2023)
This century has necessitated scholars to probe the credence of science in the news reportage of the Covid-19 pandemic. Therefore, this paper aims to establish the locus of science as treated by CNN against the backdrop of this global health crisis. Using Nisbet’s (2009) typology as the new paradigm in public engagement as informed by content analysis, this paper argues that CNN Philippines’ news articles are mostly framed as scientific/technical uncertainty which holds science with the highest esteem in decision-making, but it also disregards its authority for political reasons. As guided by Yanovitzky and Weber (2019), this paper also articulates that the functions of CNN as a news media organization in the reportage of science are mobilization and awareness which provoke action among policy actors through relevant information. Further, this paper offers a perceptive look into an emerging dimension for science communication scholars: the gulf between science and politics which surfaces the politicization of key pandemic decisions.